Relaxation of Process-Induced Stresses in Composite Parts – Mixed Experimental-Numerical Approach - GALINSKA, Anna Maria (Engineering Transactions, 2018)
The main source of the process-induced deformations are stresses which occur in composite parts during cure. Those stresses cause unexpected reduction of the part strength which may bring about catastrophic consequences. The measurements of the process-induced stresses in composite parts are very difficult, so the problem has been neglected so far. Therefore, in the scope of the present work an attempt is made to evaluate the stresses in composite parts made of carbon/epoxy unidirectional prepreg by a numerical simulation. The results of the simulation are verified by the comparison of the calculated and measured deformations of a composite part. Since the composite materials exhibit viscoelastic behaviour, some of the process-induced stresses in composite parts may be relaxed during exploitation of the part, which may lead to the decrease of the undesired process-induced stresses. Therefore, a user defined viscoelastic-orthotropic material model was developed in order to take into account the stress relaxation. Such an approach allowed to evaluate the process-induced stress level in composite parts during exploitation without difficult and time-consuming experiments.